Belly Bellows - Orojide-Isola, Akinwumi (University Press Plc, 2009)
This play is based on the Yoruba myths of the goddess Ọya with a metaphor that gives a deeper understanding of individuals and groups in situations of conflict and cooperation.
Keywords: Drama; Historical; Nigeria(English); Oya